Fatores explicativos das deficiências de controle interno - Elisangela Oliveira Rodrigues Maquiaveli (2023)
After scandals and accounting frauds in mid-2000, there was a need for greater transparency in the accounting reports disclosed by organizations, and in this sense, incentives began to be reinforced that forced entities to implement more effective internal controls, as a means of mitigating the its shortcomings, such as the SOX Law in 2002 in the USA, and in Brazil, NBCTA 265 of the CFC, IN 480/2009 of the Comissão de Valores Mobiliários. This study had the general objective of investigating the explanatory factors of Deficiencies of Internal Control (DCI) over the disclosure of financial reports of Brazilian companies listed on B3. The sample consisted of 343 companies traded on B3, in the period from 2016 to 2021, the results showed that the average of companies that disclosed DCI was 38.92%, with 33% of these companies reporting losses, 76% are audited by BIGFOUR-type companies and 57% are classified in the Governance levels (Novo Mercado, Level 1 and 2). The sectors that presented the greatest disclosures of DCI accumulated in the period were the sectors of cyclical consumption 28.75%, public utility 18.73% and Industrial Goods 16.73%. The most recurrent natures of DCI disclosure are related to Senior Management; Policies, Procedures and Accounting and Administrative Practices with 638 observations; Information, Security and Access System with 506 observations; and Accounting Records of Balance Sheet and Income Accounts with 468 observations. In panel binomial logit regression, the results showed that larger companies, with a higher MTB indicator, that report losses and are audited by BIGFOUR; companies are more likely to disclose DCI, on the other hand, older companies with growth in sales are less likely to disclose DCI. In addition, when the company has a DCI in the previous year, it will influence an increase in the probability of disclosing DCI in the next year. Regarding recurrences in the period from 2017 to 2021, there was an average of 73% disclosure of DCI recurrence and the economic sectors that showed more recurrences were: Cyclical Consumption 29.38%, Public Utility 19.92% and Industrial Goods 16 .72%. It is inferred, in the binomial logit regression, that the companies that have a higher probability of recurrence of DCI disclosure, are the oldest and that report losses, on the other hand, companies with sales growth, have a lower probability of recurrence of disclosure from DCI. In the linear regression, which measured the factors that influence the amount of DCI disclosure, the findings suggest that older companies, with sales growth, and better profitability have a greater amount of DCI disclosure, whereas larger entities and with a higher index of indebtedness, have less disclosure of DCI. In view of the results, the importance of this research is revealed, since by identifying the explanatory factors of DCI disclosures, measures can be used to mitigate deficiencies, reducing errors and fraud, making companies more productive and more competitive in the market. This study contributes to information users, investors, market agents, helping to understand the factors that may influence the disclosure of DCI, and helps regulatory bodies to assess the factors that have an impact on the disclosure of DCI, and can analyze the need to obtain new information in the most informative and transparent Reference Form.